Preparation and characterization of hybrid nanomaterials containing magnetic fe3o4 nanoparticles as drug delivery system - DEMİR, SERAP (My University, 2022)
In this study, magnetic Fe3O4 nanoparticles were synthesized and the magnetic surfaces of the nanoparticles were modified with thiol groups. The chitosan polymer was modified with allyl groups and then bound to magnetic nanoparticles by the thiol-en click reaction. The drugs paclitaxel (PTX) and doxorubicin (DOX) were loaded separately and together into this prepared hybrid material, and then drug releases from the hybrid material were studied. The aim of this paper is to present the results on the controlled release of DOX and PPT cancer drugs from chitosan-Fe3O4 nanoparticles at two different pH values (5.0 and 7.4). PTX was effectively loaded into chitosan-Fe3O4 nanoparticles and slowly released up to 72.66% at pH 5 and 41.45% at pH 7.4 after 48 hours. DOX was effectively loaded into chitosan-Fe3O4 nanoparticles and slowly released up to 30.5% at pH 5 and 23.3% at pH 7.4 after 48 hours.
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary; drug release; cancer drug; chitosan; thiol-en click; magnetic nanoparticles